To find which of the given responses is a zero of the polynomial \( g(x) = (x - 7)(3x - 5) \), we can apply the Factor Theorem, which states that if \( (x - c) \) is a factor of a polynomial, then \( c \) is a zero of the polynomial.
From the factors provided:
- \( x - 7 = 0 \) gives us \( x = 7 \).
- \( 3x - 5 = 0 \) gives us \( 3x = 5 \) or \( x = \frac{5}{3} \).
Now, let's evaluate the possible responses:
- \( x = -5 \): Not a zero
- \( x = -\frac{5}{3} \): Not a zero
- \( x = 7 \): This is a zero
- \( x = -7 \): Not a zero
Therefore, the correct answer is:
x = 7